Mechanisms of support for exclusive breastmilk expressers in the community: a scoping review - Leah Strauch; Linda Sweet; Hayley Scott; Amanda Müller (BMC, 2019)
Abstract Background The World Health Organization recommends that infants be exclusively breastfed until the age of six months. Breastfeeding is generally understood to mean the provision of human breastmilk to the infant by direct feeding at the breast, and interventions aimed at supporting exclusive breastfeeding are therefore targeted at this activity. However, breastfeeding is actually an umbrella term covering the provision of breastmilk to an infant by any means. Our population of interest is mothers who exclusively feed their infants indirectly using expressed breastmilk. Some research suggests that any expressing, and exclusively expressing in particular, can be a risk factor for early cessation of exclusive breastmilk provision, so we were interested to identify whether any specific support existed for exclusively expressing mothers outside of the context of premature infants and the Neonatal Intensive Care Unit setting. Methods A scoping review following the Joanna Briggs Institute approach was used to explore the phenomenon of formal and informal supports in the community for exclusively expressing mothers. Searches were run across academic databases and of government websites and infant feeding support organisations. Finally, an informal internet search was run using a simple search string. Results On analysis of results, there were no studies or articles that met the search criteria. An informal internet search linked us directly with websites and blogs that could be considered a form of support intervention. These informal results suggest that support material or programs could possibly exist in other modalities but we cannot find them in the context of this type of scoping review. Conclusions The results of the search corroborated what we had suspected - that exclusively expressing mothers are not specifically supported by usual channels for new parents and that it is also difficult to find acknowledgement that exclusive expression exists. The absence of results demonstrates the relevance of this study: exclusively expressing mothers are an under-served population. If we wish to strive towards achievement of World Health Organization breastfeeding goals, exclusively expressing mothers require targeted support to assist in their infant feeding experience, and there is little formal evidence of it currently being provided.